PENGARUH HARI RAYA IDUL IDUL FITRI TERHADAP INFLASI KOTA TASIKMALAYA - Milatu, Mustanginah (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2019)
Every time there is a celebration of Eid al-Fitr in our society, at that time the demand for goods and services increases. This phenomenon, if it is not balanced with adequate supply, will cause a significant increase in the prices of goods and services. The increase can occur before or after. The phenomenon of rising prices of goods and services in general is called inflation. Inflation is a very important economic indicator. Low and stable inflation will be a stimulator of economic growth. The purpose of this study was to determine the effect of Eid al-Fitr on inflation in the City of Tasikmalaya so that it is expected to help the government in determining policies related to price control. This study uses a simple linear regression analysis method with the variable to be studied is Eid al-Fitr. The data used is secondary data from the Central Statistics Agency (BPS) in 2010-2017. The results of this study indicate that Eid al-Fitr has a positive effect on inflation in the City of Tasikmalaya, the magnitude of the effect is 8.7 percent.